Students’ conceptual understanding of transformation geometry based on Van Hiele’s level assisted by GeoGebra - Luhukay, Agnes Stefine; Kodri, Riskika Fauziah; Salman, A. N. M. (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2025)
Mathematics has lower accomplishment than other subjects, according to TIMSS in 2011 and 2015 and PISA in 2015 and 2018. Geometry and measuring are the topics with the fewest right answers in the most recent National Exams, which were held in 2018 and 2019. According to the Minister of Education and Culture Regulation No. 16 of 2022, instructors must be able to use technology and communication devices in the learning process. The purpose of this study is to see how Van Hiele theory, helped by the Geogebra application, affects students' conceptual grasp of the geometry transformation topic taught in the D phase of the Merdeka Curriculum at the junior high school level. The subjects of this research were 55 students of grade IX who were divided into two groups, namely the experimental class which received learning with the application of Van Hiele theory assisted by the Geogebra application and the control class which applied conventional learning. The research was conducted using a mixed-methods approach, which combines both quantitative and qualitative methodologies. By using the Mann Whitney test on student score data of both class, it was concluded that there was no significant effect on level 0-visualization, level 1-analysis, and level 2-informal deduction, but there was a significant effect on students' abilities at level 3-deduction and level 4-rigor, which means that students who are taught using Van Hiele learning theory assisted by the Geogebra application have better conceptual understanding than students who are taught conventionally.